PENGARUH KECEPATAN ALIRAN PENDINGIN TERHADAP PANAS PEMOTONGAN PADA PEMBUBUTAN BENDA KERJA SILINDRIS - Michael Rumondor; Rudy Poeng; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2020)
The lathe machine is a machine tool that rotates a workpiece to perform cutting. Lathe it self constitutes a procces that cuts rotating workpiece used chisel that moves parallel with rotating axis. The cutting process will generate heat. The lathe machines is equipped with liquid direct contact cooling system to cooling the chisel and the workpiece. This research, observed the effect of cooling liquid flow rates toward the heat, generates by cutting procces of a cylindrical workpiece.The are two aims of this research. The first aim, is to calculate the gerenates by the cutting process of a cylindrical workpiece. The second aim, is to know the number of cooling liquid flow rates that is good to cooling the chisel and the workpiece. Experiment were done by three variations of cooling flow rates, that is regulated by the open angle of cooling liquid’s ball valve. There are three open angle variations that are 300, 600, 900.From the experiments, the used of the cooling liquid is able to cooling down the high temperature due to cutting process. At 900 open angle of cooling liquid’s ball valve showed a better effects of cooling process. However, the decreases of temperature done by 300 and 600 open angle position of cooling liquid’s ball valve are not significant. Keyword: the effect of cooling liquid flow rates toward the heat, generates by cutting procces of a cylindrical workpiece